Outcomes of patients with anemia and renal dysfunction in hospitalized heart failure with preserved ejection fraction (from the CN-HF registry). (December 2019) - Jin, Xuejuan; Cao, Juan; Zhou, Jun; Wang, Yanyan; Han, Xueting; Song, Yu; Fan, Yuyuan; Chen, Zhenyue; Xu, Dingli; Yang, Xinchun; Dong, Wei; Li, Liwen; et al.
Abstract: Background: Although a large number of studies on heart failure with reduced ejection fraction (HFrEF) have found that anemia and renal dysfunction (RD) independently predicted poor outcomes, there are still few reports on patients with heart failure with preserved ejection fraction (HFpEF). Methods: Clinical data of HFpEF patients registered in the China National Heart Failure Registration Study (CN-HF) were evaluated and the clinical features of patients with or without anemia/RD were compared to explore the impact of anemia and RD on all-cause mortality and all-cause re-hospitalization. Results: 1604 patients with HFpEF were enrolled, the prevalence of anemia was 51.0%. Although anemia was associated with increased risk of all-cause mortality and all-cause re-hospitalization in univariate COX regression (p < 0.05), multivariate COX model confirmed that anemia was not independently associated with all-cause mortality [hazard ratio (HR) 1.14, 95% confidence interval (CI) 0.85–1.52, p = 0.386] and all-cause re-hospitalization (HR 1.13, 95% CI 0.96–1.33, p = 0.152). Similarly, RD was not an independent predictor of all-cause mortality (HR 1.18, 95% CI 0.88–1.57, p = 0.269) and all-cause re-hospitalization (HR 0.94, 95% CI 0.79–1.12, p = 0.488) as assessed in the adjusted COX regression model. The interaction between RD and anemia on end-points events was also not statistically significant. However, anemia was associated with increased all-cause re-hospitalization in patients with New York Heart Association (NYHA) class III-IV. Conclusions: In patients with HFpEF from CN-HF registry, anemia was common, but was not an independent predictor of all-cause mortality and all-cause re-hospitalization, except for the all-cause re-hospitalization in patients with NYHA class III-IV. Clinical Trial Registration : http://www.clinicaltrials.gov/ct2/home ; ID: NCT02079428 .